PENGARUH URINE SAPI TERFERMENTASI DENGAN DOSIS DAN INTERVAL PEMBERIAN YANG BERBEDA TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Siti Aisyah; Novianti Sunarlim; Bakhendri Solfan (Jurnal Agroteknologi, 2011)
A research was conducted at research farm of Agriculture and Animal Science Faculty of State Islamic University Sultan Syarif Kasim Riau from April to June 2011. The objective of this research was to determine a combination of concentration and application interval of cow’s urine that maximizes the growth of chinese cabbage (Brassica juncea L.). Combinations of four cow’s urine concentration (0, 15%, 30% and 45%) and three application intervals (every 2, 3 or 4 days) were arranged in Randomized Complete Block Design (RCBD) wirh 3 replications. The experiment was conducted in pots with peat soil The plants were harvested at 40 days and data were collected for plant height, number of leaves/plant, leaf length (measured for the longest leaf), shoot fresh weight and shoot dry weight. Results of the research showed that there were no changes in plant height, number of leaves/plant and leaf length was observed for different application intervals. However, the increase of every 15% of cows’ urine concentration increased 2.7 cm plant height, 1.2 leaves/plants, and 1.5 cm leaf length. Significant interaction of concentration and application interval was observed for shoot fresh weight and shoot dry weight. A combination of 45% concentration and 2 days application interval produced the best shoot fresh weight and shoot dry weight, but there was no effect of application interval on 15% concentration.